PENGARUH PENGANGGURAN, PENGELUARAN PEMERINTAH DAN INFLASI TERHADAP KEMISKINAN DI INDONESIA TAHUN 2016-2020 - Juvico Akbar Karuniawan; Aris Soelistyo (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
This study aims to determine the effect of unemployment, government spending and inflation on poverty in Indonesia in 2016-2020 This study uses a quantitative approach. The data used is Indonesian secondary data from 2016-2020. The data analysis technique in this study uses time series data analysis with the Least Square Dummy Variable (LSDV) model. The results of the study show that: (1) The unemployment variable has a positive and significant effect on poverty by 3.559197; (2) Government expenditure variable has a negative and significant effect on poverty by -2.062619; (3) The inflation variable has a negative and insignificant effect on poverty by -0.116989; and (4) The variables of unemployment and government spending simultaneously affect poverty while the inflation variable simultaneously does not affect poverty.